2016
DOI: 10.1016/j.jvoice.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Vocal and Neural Responses to Unexpected Changes in Voice Pitch Auditory Feedback During Register Transitions

Abstract: Objective/Hypothesis It is known that singers are able to control their voice to maintain a relatively constant vocal quality while transitioning between vocal registers; however, the neural mechanisms underlying this effect are not understood. It was hypothesized that greater attention to the acoustical feedback of the voice and increased control of the vocal musculature during register transitions compared to singing within a register would be represented as neurological differences in event-related potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
10
0
3
Order By: Relevance
“…The combination of elements test signal generator, response analyser, and CAPRICEP-set and orthogonal matrix is the CAPRICEP-based method [3]. We used a Gaussian smoother 8 for LPF and fed the output to VFO (Variable Frequency Oscillator) to modulate fo of the test signals. We normalize the pitch extractor's responses by the LTI response of the lower path in Fig.…”
Section: Objective Measurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of elements test signal generator, response analyser, and CAPRICEP-set and orthogonal matrix is the CAPRICEP-based method [3]. We used a Gaussian smoother 8 for LPF and fed the output to VFO (Variable Frequency Oscillator) to modulate fo of the test signals. We normalize the pitch extractor's responses by the LTI response of the lower path in Fig.…”
Section: Objective Measurement Methodsmentioning
confidence: 99%
“…The first author introduced an altered auditory feedback technique 5 and reported that our voice pitch control consists of two responses to feedback pitch modification, the voluntary and the involuntary responses a quarter-century ago [5,6]. Despite decades of research, altered feedback still is a hot topic for investigating speech chain and underlying neural basis [7][8][9][10][11]. This research mainly focused on voluntary responses represented by the pitch shift paradigm and adaptation paradigm [12][13][14].…”
Section: Backgoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The first author introduced an altered auditory feed-back technique 1 and reported that our voice fundamental frequency (fo) 2 responds to feedback pitch modification [4]. Despite decades of research, altered feedback still is a hot topic for investigating speech chain and underlying neural basis [5][6][7][8][9]. Those research focused on voluntary responses represented by the pitch shift paradigm and adaptation paradigm [10,11].…”
Section: Backgoundmentioning
confidence: 99%
“…The fundamental frequency (fo) 1 of sustained vowels respond to frequency modulation of aurally presented sounds [2][3][4]. This response, combined with our recently developed system analysis method [5,6] provides a versatile new tool for investigating the auditory-to-speech chain.…”
Section: Introductionmentioning
confidence: 99%